2022
DOI: 10.1039/d2fo02336a
|View full text |Cite
|
Sign up to set email alerts
|

The combination of microbiome and metabolome to analyze the cross-cooperation mechanism ofEchinacea purpureapolysaccharide with the gut microbiotain vitroandin vivo

Abstract: Echinacea purpurea polysaccharide (EPP) is a functional compound in Echinacea purpurea. At the present, it is generally recognized that plant polysaccharides can regulate the intestinal microecology, but there are few...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Natural polysaccharides participate in the multiple functions of host–microbe symbiosis in the gut, such as promoting the growth and activity of probiotics in the gut. It was reported that Echinacea purpurea polysaccharide (EPP) can regulate gut microbial diversity by increasing the abundance of Bifidobacterium and Streptococcus , while also reducing the abundance of Prevotella , Catenibacterium , and Ruminococcus torques [ 115 ]. It is noteworthy that the supplementation of Eucommiae cortex polysaccharides (EPs) can remarkably alleviate behavioral disturbances in mice by reducing the ratio of Firmicutes to Bacteroidetes , inhibiting the expansion of Escherichia coli , and promoting the growth of SCFAs-producing bacteria, including Butyricicoccus , Fibrobacter , and Roseburia , in the gut microbiome [ 116 ].…”
Section: Polysaccharides Ameliorate Fatigue Via the Gut-muscle Axismentioning
confidence: 99%
See 3 more Smart Citations
“…Natural polysaccharides participate in the multiple functions of host–microbe symbiosis in the gut, such as promoting the growth and activity of probiotics in the gut. It was reported that Echinacea purpurea polysaccharide (EPP) can regulate gut microbial diversity by increasing the abundance of Bifidobacterium and Streptococcus , while also reducing the abundance of Prevotella , Catenibacterium , and Ruminococcus torques [ 115 ]. It is noteworthy that the supplementation of Eucommiae cortex polysaccharides (EPs) can remarkably alleviate behavioral disturbances in mice by reducing the ratio of Firmicutes to Bacteroidetes , inhibiting the expansion of Escherichia coli , and promoting the growth of SCFAs-producing bacteria, including Butyricicoccus , Fibrobacter , and Roseburia , in the gut microbiome [ 116 ].…”
Section: Polysaccharides Ameliorate Fatigue Via the Gut-muscle Axismentioning
confidence: 99%
“…EPP not only promotes the proliferation of gut-beneficial bacteria, but also stimulates the beneficial bacteria to metabolize polysaccharides and produce valuable metabolites, including tyrosine, tryptophan, beta-D-fructose 1,6-biphosphate, etc. [ 115 ]. There is growing opinion that the metabolites produced by microbes using polysaccharides are key players in gut integrity and host health.…”
Section: Polysaccharides Ameliorate Fatigue Via the Gut-muscle Axismentioning
confidence: 99%
See 2 more Smart Citations
“…Caffeic acid derivatives, such as chicoric acid, chlorogenic acid, and caftaric acid, present in Echinacea purpurea, primarily exhibit antioxidant, anti-allergic, anti-inflammatory, anti-ulcer, and antiviral effects (Ye et al, 2019;de Oliveira et al, 2021;Ravazzolo et al, 2022). The polysaccharides in Echinacea purpurea contribute to various beneficial effects, including antioxidant, anti-tumor, antiviral, antibacterial, hypoglycemic, liver protection, immune regulation, and gastrointestinal protection (Jiang et al, 2021;Liu et al, 2020Liu et al, , 2022Shi et al, 2021). However, numerous studies have demonstrated the immunomodulatory, antibacterial, antiviral, anti-inflammatory, and antioxidant therapeutic effects of Echinacea (Wang et al, 2024).…”
Section: Introductionmentioning
confidence: 99%